From Pollution to Power: Transforming Rice Straw into Torrefied Biomass Pellets for Sustainable Energy in NCR - Vikas Kikan,; Dr. Smitha Girija, (The Bioscan, 2025)
The National Capital Region (NCR) of India endures some of the world’s worst air quality levels each winter, primarily due to the large-scale burning of rice stubble in the adjoining states of Punjab, Haryana, and Western Uttar Pradesh. This seasonal agricultural practice, though widespread, results in severe public health hazards, economic losses, and environmental degradation. This research addresses the root of this issue by proposing a viable, circular economy-based solution: the conversion of rice straw into torrefied biomass pellets for use as a substitute fuel in coal-fired thermal power plants. Torrefaction—a thermal pre-treatment technology—enhances the energy density, storability, and combustibility of agricultural biomass, offering a clean and carbon-neutral alternative to fossil fuels. This paper presents a comprehensive analysis of the environmental implications of stubble burning and the advantages of deploying torrefaction as a mitigation strategy. A detailed case study of Beyond Drilling & Exploration Private Limited, the largest torrefied biomass pellet producer in India, highlights how decentralized pellet production, strategic plant location, and public-private collaboration can effectively manage biomass residues while creating rural employment and reducing emissions. The research also evaluates the policy ecosystem, focusing on progressive initiatives like the Haryana Biomass Policy 2018 and the biomass co-firing mandate by NTPC and other thermal power plants. Quantitative data drawn from field operations illustrates significant reductions in PM2.5, PM10, and GHG emissions, along with increased fuel efficiency and reduced coal consumption in co-fired power plants. The paper concludes with actionable recommendations for scaling up this model across India through supportive regulatory frameworks, capital incentives, farmer awareness programs, and localized pellet hubs. By turning a persistent pollution source into a sustainable energy input, this model offers a replicable blueprint for addressing India’s twin challenges of air pollution and energy transition.